Jualan Kopi di Pinggir Jalan pada Lima Wirausaha Kedai Kopi di Kota Kendari - Muhammad Sawal Rudi Yanto; Nasrudin Suyuti; Raemon Raemon (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to determine and analyze the adaptive strategies developed by roadside coffee shop entrepreneurs in several districts such as Kadia, Mandogga, and Abeli districts in Kendari City, Southeast Sulawesi Province. The theory used is the theory of socio-cultural adaptation strategies, put forward by Jhon William Bennet (1976). using ethnographic methods with data collection carried out using techniques of involved observation and in-depth interviews. The data obtained were analyzed descriptively and qualitatively, the analysis was carried out to simplify the data obtained in the research into a form that is easier to read and interpret. The results of this study show how the forms of adaptive strategies of coffee shop entrepreneurs in the city of Kedari, in maintaining the coffee shop business they have from the competition of other coffee shop owners in Kendari City.